Penguasaan Tanah Pantai dan Wilayah Pesisir di Indonesia - Muhammad Ilham Arisaputra (Faculty of Law Hang Tuah University, 2015)
The beach is the junction between the highest tide and the mainland, while the coastal area is the transition between terrestrial and marine ecosystems that is affected by changes in land and sea. The utilization of coastal areas and small islands in Indonesia is regulated in Act Number 27 of 2007 on the Management of Coastal Areas and Small Islands that is last amended into Act Number 1 of 2014, and is also based on Basic Act on Agrarian. Utilization of coastal waters is given in the form of rights to enterprise the coastal waters, namely the rights on certain parts of the coastal waters to enterprise marine resources and fisheries, as other business related to the utilization of coastal resources and the small islands covering sea level and water column over surface of the sea floor at a certain breadth limit. The coastal land in the coastal areas can essentially be owned by or be the right of a person or legal entity. Owning and authorizing the coastal land and utilizing the coastal areas should certainly pay attention to and be compatible with the spatial planning of regencies or cities.